Leucocyte and Platelet‐rich Fibrin: a carrier of autologous multipotent cells for regenerative medicine. Issue 3 (5th January 2018) - Di Liddo, Rosa; Bertalot, Thomas; Borean, Alessio; Pirola, Ivan; Argentoni, Alberto; Schrenk, Sandra; Cenzi, Carola; Capelli, Stefano; Conconi, Maria Teresa; Parnigotto, Pier Paolo
Abstract: The wound healing is a complex process wherein inflammation, proliferation and regeneration evolve according to a spatio‐temporal pattern from the activation of coagulation cascade to the formation of a plug clot including fibrin matrix, blood‐borne cells and cytokines/growth factors. Creating environments conducive to tissue repair, the haemoderivatives are commonly proposed for the treatment of hard‐to‐heal wounds. Here, we explored in vitro the intrinsic regenerative potentialities of a leucocyte‐ and platelet‐rich fibrin product, known as CPL‐MB, defining the stemness grade of cells sprouting from the haemoderivative. Using highly concentrated serum‐based medium to simulate wound conditions, we isolated fibroblast‐like cells (CPL‐CMCs) adhering to plastic and showing stable in vitro propagation, heterogeneous stem cell expression pattern, endothelial adhesive properties and immunomodulatory profile. Due to their blood derivation and expression of CXCR4, CPL‐CMCs have been suggested to be immature cells circulating in peripheral blood at quiescent state until activation by both coagulation event and inflammatory stimuli such as stromal‐derived factor 1/SDF1. Expressing integrins (CD49f, CD103), vascular adhesion molecules (CD106, CD166), endoglin (CD105) and remodelling matrix enzymes (MMP2, MMP9, MMP13), they showed a transendothelial migratory potential besides multipotency. Taken together, our data suggested that a standardized, reliable and economically feasible blood product such as CPL‐MB functions as an artificial stem cell niche that, under permissive conditions, originate ex vivo immature cells that could be useful for autologous stem cell‐based therapies.